2022
DOI: 10.3389/fphys.2021.802584
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Multiple P450 Genes and Their Co-factor CPR in the Development of Permethrin Resistance in the Mosquito Culex quinquefasciatus

Abstract: Mosquitoes’ increasing resistance to insecticides is becoming a major threat for control efforts worldwide. Multiple P450 genes that are up-regulated in permethrin resistant strains of Culex quinquefasciatus have been linked to the development of resistance. In the current study, we characterized the function of six P450 genes, CYP6P14, CYP6BZ2, CYP9J33, CYP9J34, CYP9J40, and CYP9J45, that are overexpressed in the permethrin resistant Culex mosquitoes and showed their capability in metabolism of permethrin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…For instance, CYP9J33 , CYP9J40 , and CYP9J45 are overexpressed and demonstrate the ability to metabolize insecticide in permethrin‐resistant Cx. quinquefasciatu s 48 . In addition, the expression level of CYP9M5 increased 54‐fold in resistant strains of Aedes aegypti 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CYP9J33 , CYP9J40 , and CYP9J45 are overexpressed and demonstrate the ability to metabolize insecticide in permethrin‐resistant Cx. quinquefasciatu s 48 . In addition, the expression level of CYP9M5 increased 54‐fold in resistant strains of Aedes aegypti 24 .…”
Section: Discussionmentioning
confidence: 99%
“…quinquefasciatus. 48 In addition, the expression level of CYP9M5 increased 54-fold in resistant strains of Aedes aegypti. 24 Moreover, previous studies have identified that deltamethrin can be metabolized by Anopheles gambiae-resistant strains CYP9K1 and CYP9J5.…”
Section: Discussionmentioning
confidence: 99%
“…Cpr , also known as NADPH cytochrome P450 reductase (AGAP000500), is an essential electron donor in P450-mediated reactions, including insecticide metabolism. Increased Cpr expression has been implicated in insecticide resistance in Culex (Gong et al ., 2022), and knockdown of the gene has been demonstrated to elevate permethrin susceptibility in An. gambaie (Lycett et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The NADPH cytochrome P450 reductase is also an electron transfer protein found in the endoplasmic reticulum of cells. NADPH cytochrome P450 reductase and cytb5 have been co-expressed in some instances [ 41 ]. Marcombe et al [ 42 ] have reported the overexpression of NADPH cytochrome P450 reductase in insecticide-resistant Ae .…”
Section: Discussionmentioning
confidence: 99%